2015
DOI: 10.1007/s10854-015-4068-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and photodegradation activity of hollow Zn1−x Ni x Fe2O4 sphere

Abstract: Carbon microspheres with good dispersibility were synthesized by hydrothermal method using glucose as raw material. Taking the as-prepared carbon microsphere as the template, a series of hollow Zn 1-x Ni x Fe 2 O 4 spheres (x = 0-1 with interval of 0.2) were prepared by chemical precipitation method. The composition, morphology, electrical and magnetic properties of the hollow Zn 1-x Ni x Fe 2 O 4 spheres were characterized. The results of nitrogen adsorption-desorption isotherms indicates that the Zn 1-x Ni x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 44 publications
(38 reference statements)
0
13
0
Order By: Relevance
“…Moreover, further increasing the cerium content on the BiVO 4 surface will lead to decrease of the photocatalytic performance under visible-light. Three plausible reasons were thought to result in this finding: (i) excess CeO x may cover the active sites on the BiVO 4 surface and thereby reduce the charge-separation efficiency [31,32]; (ii) excess CeO x may be the recombination center of the photogenerated electron-holes because of the short-circuiting mechanism [33]; and (iii) the size of the composite photocatalysts obviously increased when the cerium content was up to 9 wt.% (Fig. 2(D), Table 1), which then may reduce the transmission efficiency of photogenerated electron-holes to the composite surface.…”
Section: Effect Of Ce On the Photocatalytic Propertiesmentioning
confidence: 99%
“…Moreover, further increasing the cerium content on the BiVO 4 surface will lead to decrease of the photocatalytic performance under visible-light. Three plausible reasons were thought to result in this finding: (i) excess CeO x may cover the active sites on the BiVO 4 surface and thereby reduce the charge-separation efficiency [31,32]; (ii) excess CeO x may be the recombination center of the photogenerated electron-holes because of the short-circuiting mechanism [33]; and (iii) the size of the composite photocatalysts obviously increased when the cerium content was up to 9 wt.% (Fig. 2(D), Table 1), which then may reduce the transmission efficiency of photogenerated electron-holes to the composite surface.…”
Section: Effect Of Ce On the Photocatalytic Propertiesmentioning
confidence: 99%
“…1(b) shows the V2p3/2 XPS spectra of the samples. The asymmetrical V 2p3/2 signal could be decomposed into two components: 516.3 and 516.8 eV for CS-BiVO 4 and 516.6 and 517.1 eV for 0.04B CS-BiVO 4 , which were assigned to the surface V 4 þ and V 5 þ [21], respectively. The molar ratio of the surface V 4 þ /V 5 þ (1.93) on the 0.04B CS-BiVO 4 sample was higher than that of the CS-BiVO 4 sample (0.75).…”
Section: Xps Analysismentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11] Photocatalytic properties depend on the photo-excited carries transport characteristics, and this is a disadvantage of pure BiVO 4 . To solve this problem, various strategies have been proposed, including doping with metals [12][13][14] or nonmetals, 15 heterojunction structure formation, [16][17][18][19][20] and the use of co-catalysts [21][22][23][24] etc. In 1986, Sato et al 25 rst doped N into TiO 2 , and found that the photocatalytic activities of N-doped TiO 2 in oxygen isotope equilibration and oxidation of carbon monoxide and ethane were higher than those of standard TiO 2 in the visible light region (434 nm).…”
Section: Introductionmentioning
confidence: 99%